# 1950 AHSME Problems/Problem 24

## Problem

The equation $x + \sqrt{x-2} = 4$ has: $\textbf{(A)}\ 2\text{ real roots }\qquad\textbf{(B)}\ 1\text{ real and}\ 1\text{ imaginary root}\qquad\textbf{(C)}\ 2\text{ imaginary roots}\qquad\textbf{(D)}\ \text{ no roots}\qquad\textbf{(E)}\ 1\text{ real root}$

## Solutions

### Solution 1 $x + \sqrt{x-2} = 4$ Original Equation $\sqrt{x-2} = 4 - x$ Subtract x from both sides $x-2 = 16 - 8x + x^2$ Square both sides $x^2 - 9x + 18 = 0$ Get all terms on one side $(x-6)(x-3) = 0$ Factor $x = \{6, 3\}$

If you put down A as your answer, it's wrong. You need to check for extraneous roots. $6 + \sqrt{6 - 2} = 6 + \sqrt{4} = 6 + 2 = 8 \ne 4$ $3 + \sqrt{3-2} = 3 + \sqrt{1} = 3 + 1 = 4 \checkmark$

There is $\boxed{\textbf{(E)} \text{1 real root}}$

### Solution 2

It's not hard to note that $x=3$ simply works, as $3 + \sqrt{1} = 4$. But, $x$ is increasing, and $\sqrt{x-2}$ is increasing, so $3$ is the only root. If $x < 3$, $x + \sqrt{x-2} < 4$, and similarly if $x > 3$, then $x + \sqrt{x-2} > 4$. Imaginary roots don't have to be considered because squaring the equation gives a quadratic, and quadratics either have only imaginary or only real roots.

### Solution 3

We can create symmetry in the equation: $$x+\sqrt{x-2} = 4$$ $$x-2+\sqrt{x-2} = 2.$$ Let $y = \sqrt{x-2}$, then we have $$y^2+y-2 = 0$$ $$(y+2)(y-1) = 0$$ The two roots are $\sqrt{x-2} = -2, 1$.

Notice, that the first root is extraneous as the range for the square root function is always the non-negative numbers (remember, negative numbers in square roots give imaginary numbers - imaginary numbers in square roots don't give negative numbers); thus, the only real root for $x$ occurs for the second root; squaring both sides and solving for $x$ gives $x=3 \Rightarrow \boxed{\textbf{(E)} \text{1 real root}}$.

~Vndom

The problems on this page are copyrighted by the Mathematical Association of America's American Mathematics Competitions. 